Autochthonous and Probiotic Lactic Acid Bacteria Employed for Production of “Advanced Traditional Cheeses” - Vincenzina Fusco; Grazia Marina Quero; Palmiro Poltronieri; Maria Morea; Federico Baruzzi (Foods, 2019)
Microbial characterization of two Italian traditional cheeses, Giuncata and Caciotta Leccese, was carried out, with the aim to isolate autochthonous bacterial strains to be used as starters to improve and standardize the quality of these cheeses. More than 400 bacterial isolates were found, using PCR-based identification, to belong to 12 species of the Streptococcus, Lactococcus, Lactobacillus, and Leuconostoc genera. The dominant strains were screened for antagonistic activity against pathogenic and spoilage bacteria and exopolysaccharide production, acidification, and proteolytic activity. Since Streptococcus macedonicus was found to be the most prevalent lactic acid bacteria species present in milk and in both types of cheese, the best performing strain of this species was successfully used, alone or in combination with a selected autochthonous Lactococcus lactis strain, in pilot-scale productions of Giuncata and Caciotta Leccese cheeses, respectively. The combined inoculums of selected autochthonous strains positively influenced the sensory characteristics of both Giuncata and Caciotta cheeses. Finally, the selected autochthonous cultures were enriched with a potentially probiotic Lactobacillus rhamnosus strain and successfully used in pilot-scale productions of these traditional cheeses. To the best of our knowledge, this is the first study reporting the use of an autochthonous S. macedonicus strain as a starter for the production of cheeses with added probiotics. In addition, the identification of the probiotic strain in the feces of healthy volunteers fed with the advanced traditional cheese proved its effectiveness as a carrier for the delivery of probiotics to the human body.